Conflict Mitigation and Coping Mechanism Strategy for New Students at API ASRI Tegalrejo Islamic Boarding School - Sovi Ul Ngaini; Dahlia; Ali Rohmat (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
The transition period of new students in the pesantren environment is often colored by various adaptation problems, such as homesickness, interpersonal conflicts, social anxiety, and difficulties adjusting to a disciplined and structured dormitory life system. If not managed properly, this condition can hinder the self-adjustment process and affect the psychological well-being of students. This study aims to analyze the conflict mitigation strategies implemented by the management and examine the coping mechanism used by new students in dealing with pressure during the adaptation period at the Syubbanul Wathon Tegalrejo Islamic Boarding School. The research uses a qualitative approach with a case study method. Data were obtained through passive participatory observation, in-depth interviews, and documentation of six new students, two roommates, one security administrator, and the head of the purposively selected boarding school. Data analysis was carried out using the Miles, Huberman, and Saldana models through the stages of data condensation, data presentation, and conclusion drawn, and strengthened by triangulation of sources and techniques. The results of the study showed that the administrators applied five conflict management styles based on the Thomas-Kilmann Conflict Mode Instrument (TKI), namely competition, collaboration, compromise, avoidance, and adaptive accommodation according to the characteristics of the students' problems. Meanwhile, new students use two forms of coping mechanisms, namely emotion-focused coping and problem-focused coping which develop gradually during the adaptation process. The novelty of this research lies in the integration of the Thomas-Kilmann and Lazarus-Folkman perspectives in explaining the relationship between management conflict mitigation, social support, coping mechanisms, and the success of student adaptation. These findings imply that pesantren management needs to integrate discipline, social assistance, and psychological support to create a more adaptive and mentally healthy educational environment.